Hungary – past, present and future – from an Olympic point of view - Heim, Attila (Πανεπιστήμιο Πελοποννήσου, 2013)
Hungary has always played an important role within the world’s sport community since the International Olympic Committee was founded. The 168 gold, 146 silver and 165 bronze medals which were won by Hungarian athletes speak eloquently for themselves illustrating the achievement and international position of the Hungarian sport. A successful period of the Hungarian sport in terms of the won medals at Summer Olympic Games has started after the World War II and is still going on nowadays. But not only the athletes have achieved great results but also the Hungarian sports leaders have had an influence on the international sport governance. Starting with the presence of Ferenc Kemény, Hungarian founding member of the International Olympic Committee and today there are also two IOC members from Hungary representing the country. The country that has not only a vital sport life but also has millions of inhabitants who are committed to the Olympic Movement which can be thanked to the work of the Hungarian Olympic Committee (HOC), the National Olympic Academy of Hungary (NOA) and the sponsors who make the Olympic Brand more widespread in Hungary. One thing which could make Olympism more popular in Hungary is hosting the Games. In order to do so a feasibility study has been written to prepare for organizing the Olympic Games in Budapest. This is Hungary: past, present and future from an Olympic point of view.
Keywords: Sports - Hungary; Olympic movement; Olympism - Hungary; Olympics - Hungary; Αθλητισμός - Ουγγαρία; Olympic games - Hungary; Αθλητισμός - Ουγγαρία; Ολυμπιακό κίνημα; Ολυμπισμός - Ουγγαρία; Ολυμπιακοί αγώνες - Ουγγαρία; Ολυμπιακά αθλήματα - Ουγγαρία